Síntese e propriedades fotofísicas de bases de schiff e 1,3-benzoxazinas derivadas de 6-amino-4-(trifluormetil)quinolinas - Rocha, Inaiá Oliveira da (2020)
The present work describes the synthesis, structural study and evaluation of the photophysical properties of new Schiff bases, (E)-2-(((2-(alkyl/aryl/heteroaryl)-4-trifluormethyl)quinolin-6-il)imino)methyl)phenols, as well as their application in the construction of novel systems 3-(2-(alkyl/aryl/heteroaryl)-4-(trifluormethyl)quinolin-6-yl)-3,4-dihydro-2H-benzo[e][1,3]oxazine. Structural and electronic properties were investigated by 1H, 13C, 19F NMR and by single-crystal X-ray diffraction. Initially, a series of (E)-2-(((2-(alkyl/aryl/heteroaryl)-4-trifluormethyl)quinolin-6-il)imino)methyl)phenols (10-14), obtained from reactions between 4-(trifluormethyl)quinolin-6-amines (4a-f) and substituted salicylaldehydes (5-9), in yields of 20-91%. In sequence, the photophysical properties of absorption, emission, quantum fluorescence yield, Stokes displacement, photostability and singlet oxygen quantum yield assays of Schiff bases 10-14 were evaluated. Subsequently, the Schiff's bases (10-14) were subjected to an imine function reduction reaction using NaBH4 as a reducing agent, leading to the formation of an unprecedented series of 2-(((2-(alkyl/aryl/heteroaryl)-4-(trifluoromethyl)quinolin-6-yl)amino)methyl)phenols (15-19) in yields of 51-98%. Finally, the amines originated 15-19 were used, in the presence of formaldehyde (20) in Mannich type cyclization reactions in the synthesis of novel systems 3-(2-(alkyl/aryl/heteroaryl)-4-(trifluoromethyl)quinolin-6-yl)-3,4-dihydro-2H-benzo[e][1,3] oxazine (21-25), in yields of 50-95%.